The Principal Policy Formulation Models Of Learning During Covid-19 - Moh Muslim; Ani Maratus Sholihah; Elvi Rahmi (Universitas Islam Malang, 2022)
The spread of the COVID-19 outbreak in Indonesia has had a crucial impact on educational institutions. To contain the spread of COVID-19, the government has decided to close schools and implement distance education (online). The impact is that not all schools can carry out distance learning activities due to various obstacles and constraints. The purpose of this study is to conduct an in-depth investigation of the formulation of school principal policies in the implementation of Education to deal with the COVID-19 Pandemic. This research uses a qualitative approach with this type of case study. Data is collected through observation techniques, in-depth interviews, and documentation. Data analysis with interactive techniques. The study results concluded that the formulation of the principal's policy includes the following stages: problem formulation, policy agenda, alternative selection, strategic, operational, and determination.